'Almost like I am in Jail': homelessness and the sense of immobility in Cleveland, Ohio. Issue 3 (3rd May 2016) - Kerr, Daniel R.
ABSTRACT: Drawing on oral histories conducted with the Cleveland Homeless Oral History project between 1999 and 2005, the article addresses the unhoused interviewees' overwhelming sense of being immobile. This understanding spoke both to the reality of being restricted to shelters, but it also spoke to the larger feeling of being stuck and unable to escape their predicament. This subjective sense was belied by their everyday reality of constant movement. The article explores the disjuncture between the rhetoric and the embodied practice of movement and stillness. While the rhetoric of immobility spoke to their understanding of oppression, and served as a 'mobilizing' language, their resistance frequently involved establishing dwelling spaces in places where they were unwanted. In the context of homelessness in the twenty-first century, the very practice of dwelling can be a radical act through which the unhoused build power by laying claim to home.